Assessing traditional medicine in the treatment of neurological disorders in Mali: prelude to efficient collaboration - Youssoufa Maiga; Leon Samuel Moskatel; Seybou H. Diallo; Oumar Sangho; Housseini Dolo; Fatoumata Konipo; Salimata Diallo; Awa Coulibaly; Mariam Daou; Modibo Sangaré; Thomas Coulibaly; Adama Sissoko; et al. (BMC, 2024)
Abstract Introduction Neurological disorders (ND) have a high incidence in sub-Saharan Africa (SSA). In this region, systemic challenges of conventional medicine (CM) and cultural beliefs have contributed to a large utilization of traditional medicine (TM). Yet, data on TM and those who use it in the treatment of ND in SSA are scarce. Here, we systematically analyze its role as a therapy modality for ND in Mali, the socio-demographic characteristics of its users, and propose next steps to optimize the dual usages of TM and CM for patients with ND. Methods We conducted a questionnaire study in two phases. In phase one, patients with ND answered questions on their usage of and attitudes towards TM. In phase two, the TM therapists who provided care to the patients in phase one answered questions regarding their own practices for treating ND. Patients were recruited from the country's two university neurology departments. Results 3,534 of the 4,532 patients seen in the Departments of Neurology in 2019 met the inclusion criteria. Among these 3,534 patients, 2,430 (68.8%) had previously consulted TM for their present ND. Patients over 60 years of age most often used TM (83.1%). By education, illiterate patients utilized TM the most (85.5%) while those with more than a secondary education used TM the least (48.6%). An income greater than the minimum guaranteed salary was associated with decreased use of traditional medicine (OR 0.29, CI 0.25-0.35, p < 0.001). Among those using TM, it was overwhelmingly thought to be more effective than CM (84.6%). Linking illness to supernatural causes and believing TM therapists had a better understanding of illnesses were the most common reasons patients used traditional medicine (82.3% and 80.5%, respectively). We then interviewed 171 TM therapists who had provided care to the patients in phase one. These providers most commonly "sometimes" (62.6%) referred patients to CM and 4.1% never had. A majority of TM providers (62.6%) believed collaboration with CM could be improved by having doctor "take into account" our existence. Conclusion Our work shows that TM plays a central role in the provision of care for patients with ND in SSA with certain cohorts using it at higher rates. Future development of treatment of ND in SSA will require optimizing TM with CM and needs buy-in from all stakeholders including conventional medicine clinicians, traditional medicine therapists, researchers, politicians, and most importantly, patients.